ESR Essentials: advanced MR safety in vulnerable patients—practice recommendations by the European Society for Magnetic Resonance in Medicine and Biology - Santini, Francesco; Pansini, Michele; Deligianni, Xeni; Caligiuri, Maria Eugenia; Oei, Edwin H. G. (European radiology, 2025)
For every patient, the MR safety evaluation should include the assessment of risks in three key areas, each corresponding to a specific hazard posed by the electromagnetic fields generated by the MR scanner: ferromagnetic attraction and displacement by the static field; stimulation, acoustic noise, and device interaction by the gradient fields; and bulk and focal heating by the radiofrequency field. MR safety guidelines and procedures are typically designed around the “average” patient: adult, responsive, and of typical habitus. For this type of patient, we can safely expect that a detailed history can identify metallic objects inside and outside the body, verbal contact during the scan can detect signs of discomfort from heating or acoustic noise, and safety calculations performed by the scanner can prevent hyperthermia. However, for some less common patient categories, these assumptions do not hold. For instance, patients with larger habitus, febrile patients, or pregnant people are more subject to bulk heating and require more conservative MR protocols, while at the same time presenting challenges during positioning and preparation. Other vulnerable categories are infants, children, and patients unable to communicate, who might require screening for ferromagnetic objects with other imaging modalities or dedicated equipment. This paper will provide guidance to implement appropriate safety margins in the workflow and scanning protocols in various vulnerable patient categories that are sometimes overlooked in basic MR safety guidance documents. Clinical relevance statement Special care in the implementation of MR safety procedures is of paramount importance in the handling of patients. While most institutions have streamlined operations in place, some vulnerable patient categories require specific considerations to obtain images of optimal quality while minimizing the risks derived by exposure to the MR environment. Key Points Patients unable to effectively communicate need to be carefully screened for foreign objects . Core temperature management is important in specific patient categories . There are no hard quantitative criteria that make a patient fall into a specific vulnerable category. Protocols and procedures need to be adaptable .